Sampling-type sets and composition operators on bloch-type spaces1 (2011)
The purpose of this article is to survey the recent results on sampling-type sets and composition operators on Bloch{type spaces. Most of them were presented by the authors in two conferences held in Bogota 2011, on the occasion of celebrating the 60th anniversary of the Departamento de Matemáticas, Universidad Nacional de Colombia.